Complexity and coding lifestyle talk in GP consultations - Sarah J White; Lola Kruszelnicki; Taylor Grunsell; Conor Gilligan (Health Literacy and Communication Open)
Background Lifestyle risk factors, such as smoking, poor nutrition, alcohol use, and sedentary behaviour, are considered key intervention targets in general practice (GP). While GP consultations are well suited to preventative interventions, it is reported that GPs often miss these opportunities to pursue such discussions.Aims In investigating how “missed” such opportunities are, we identified several methodological challenges. This paper presents an exploration into these challenges, with an aim of sharing the analytic process and how such challenges might be prepared for and responded to in future research.Methods Using a dataset of 45 GP consultations recorded in 2018, we used an inductive approach informed by linguistic ethnography and conversation analysis. The study sought to identify potential missed opportunities for discussing lifestyle changes, and how these were situated within the overall structure of GP consultations as per the Calgary-Cambridge Guide.Results Through the research process, we encountered four specific challenges relating to: collection building, definition of codes, interactional barriers, and clinical and systemic barriers to lifestyle talk. The analysis reflected the complexity in researching such phenomena, particularly when trying to identify patterns within the inherently varied nature of GP and its impact on longitudinal relationships.Discussion Reflections on the research process and the results of our research underscore the interactional, clinical, and systemic complexities of GP consultations. We emphasise the need for methodological flexibility to accurately apply research to clinical practice and highlight the importance of considering the full scope of communication complexities when designing healthcare communication studies.